Reconceptualization of The Competence to be held Responsible in National Criminal Code - Ikhsan Alfarisi; Fina Afriani; Yasmir Yasmir (LAW REFORM, 2021)
Construction of norm in determining competence to be responsible stated in Criminal Code (KUHP) needs to be reconceptualized because the construction does not make any qualification on the incompetence to be responsible (verminderde teorekeningsvatbaarheid) in criminal science law. . Criminal Code stipulates that a person is deemed incompetence to be responsible for the crime he/she commits for 2 (two) reasons. First is if the person is considered mentally incapable (gebrekkige ontwikkeling), and the second is if a person is considered incapable because of an illness (ziekelijke storing). This article aims to reconceptualize the competence to be responsible stated in National Criminal Code through qualitative literature study on some texts. The finding of the study is that first, the concept of norm competence to be responsible stated in Criminal Code is no longer relevant with current development of psychiatry and law which have been specialized and interdisciplinary. The second is that the categorization of a person’s mental condition considered light and severe mental retard and has given chance for the concept of incompetence to be responsible (verminderde teorekeningsvatbaarheid), which so far is only recognized in criminal study, to be normatively present in light mental retard category and to give a chance to negatief wettelijk evolution in the study of criminal procedure to move to positief wettelijk on the superego of judge’s decision based on visum et repertum psychiatry of a psychiatrist.